2009
DOI: 10.3892/or_00000371
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional differential in-gel electrophoresis for identification of gastric cancer-specific protein markers

Abstract: Abstract. Gastric cancer is the second most common fatal malignancy in the world. Proteomics studies of clinical tumor samples have led to the identification of specific protein markers of gastric cancer detection and better understanding the carcinogenesis of gastric cancer. Gastric cancer tissue of epithelial origin and adjacent normal mucosa were examined in pair by fluorescence 2-D differential in-gel electrophoresis proteomics analysis utilizing 2-D PAGE protein separation. Intensity changes of 33 spots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Previous research showed that MMP2 and MMP9 can hydrolyze the extracellular matrix and promote invasion of tumor cells. 39 Our results demonstrated that the expression of MMP2 was significantly enhanced in 6-10B and CNE-2 cells following the overexpression of TIM-3. The expression of MMP9 was obviously enhanced in 6-10B cells.…”
Section: Dovepresssupporting
confidence: 52%
“…Previous research showed that MMP2 and MMP9 can hydrolyze the extracellular matrix and promote invasion of tumor cells. 39 Our results demonstrated that the expression of MMP2 was significantly enhanced in 6-10B and CNE-2 cells following the overexpression of TIM-3. The expression of MMP9 was obviously enhanced in 6-10B cells.…”
Section: Dovepresssupporting
confidence: 52%
“…This HVEM signature is essentially a mixture of genes involved in melanoma proliferation (MITF, CAPN3, MLANA, GNPTAB, CPN1, SOX10, and GYPC 40,41 ) and of genes involved in invasive melanoma features (CITED1, 42 ACP5, 43 LZTS1, 44 GAB2, 45 SNX10, 46 and RXRG 26,36 ); among these, it is interesting to note that targeting RXR signaling may delay relapse in melanoma 47 and that the MXI1 hypoxia responsive 48 gene is a putative tumor suppressor gene involved in melanoma progression. 35 Among the remaining genes, GAS7, ALX1, and S100AI were reported in the Rambow melanoma signature, 41 but their respective role(s) in melanocyte lineage biology is unclear.…”
Section: Genes Co-expressed With Hvem Are Associated With Aggressive mentioning
confidence: 99%